The Sustainability of Religious Moderation Policies: A Total Quality Management Analysis at IAIN Pontianak - Ranti, Utin Darma; Wahab, Wahab; Ningrum, Saumi Setya (Pascasarjana IAIN Kudus, 2026)
Research on religious moderation in higher education has generally focused on program implementation and the internalization of values. However, studies examining policy sustainability as a determinant of long-term continuity are limited. Additionally, few scholars have examined religious moderation policies using the AGIL framework developed by Talcott Parsons and Total Quality Management (TQM). This study examines the sustainability of religious moderation policies at IAIN Pontianak through the AGIL framework and TQM perspectives, and their implications for educational quality. The study employed a qualitative case study design. Data were collected through observations, in-depth interviews, and document analysis and were analyzed using thematic analysis. The findings suggest that policy sustainability is supported by adapting to national policies, integrating religious moderation into academic activities, coordinating with other institutions, and fostering a culture of continuous improvement. However, the main challenges include limited data-driven evaluation and quality indicator implementation. This study’s novel contribution is its use of the AGIL framework and TQM as an analytical framework for understanding policy sustainability, thereby extending the theoretical discourse on higher education policy implementation.Keywords: Religious Moderation, Educational Quality, AGIL, Total Quality Management, IAIN Pontianak